Propagation of underwater noise from an offshore seismic survey in Australia to Antarctica: Measurements and modelling - Gavrilov, Alexander (2017)
An offshore seismic survey was conducted over the western edge of the continental shelf in Bass Strait in 2006. Underwater noise from this survey was recorded on an autonomous sound recorder deployed in the Southern Ocean on the Antarctic continental slope. Sound emission and propagation models were verified by experimental measurements based on parameters and position of the airgun array and characteristics of the underwater sound channel. A parabolic equation approximation method was used to calculate the sound field over the continental slope of Australia and then a normal mode model was employed to account for the transmission loss due to sound scattering by surface waves south of the Polar front. The numerical predictions are consistent with the measurement results within a few dBs for the sound exposure and energy spectral levels. It is also demonstrated by measurements and modelling that the best coupling of a near-surface sound source with the SOFAR underwater sound channel takes place when the source is located over the continental slope at a sea depth of about half of the channel's axis depth. The model can be used to predict masking effects of man-made underwater noise on the communication environment of marine mammals in Antarctica.